2013
DOI: 10.1177/1091581813514282
|View full text |Cite
|
Sign up to set email alerts
|

A 13-Week Dermal Repeat-Dose Neurotoxicity Study of Hydrodesulfurized Kerosene in Rats

Abstract: A 13-week dermal repeat-dose toxicity study was conducted with hydrodesulfurized (HDS) kerosene, a test material that also met the commercial specifications for aviation turbine fuel (jet A). The objectives were to assess the potential for target organ toxicity and neurotoxicity. The HDS kerosene was applied to the shaved backs of Sprague-Dawley CD rats, 12/sex/group, 6 h/d, 5 d/wk in doses of 0 (vehicle control), 165 mg/kg (20% HDS kerosene), 330 mg/kg (40% HDS kerosene), or 495 mg/kg (60% HDS kerosene). Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…There were no changes in functional observations or motor activity and no pathological changes in nervous system tissue in a study involving repeated dermal application of hydrodesulfurized kerosene at levels up to 495 mg/kg/day (Breglia et al 2014). …”
Section: Neurotoxicitymentioning
confidence: 99%
See 4 more Smart Citations
“…There were no changes in functional observations or motor activity and no pathological changes in nervous system tissue in a study involving repeated dermal application of hydrodesulfurized kerosene at levels up to 495 mg/kg/day (Breglia et al 2014). …”
Section: Neurotoxicitymentioning
confidence: 99%
“…The C9 and C10 aliphatic constituents have been shown to produce acute CNS effects (Carpenter et al 1978, Nilsen et al 1988), but no effects were reported in studies with higher molecular weight constituents (Bowen andBalster 1998, Nilsen et al 1988). No neurological effects were reported in repeated inhalation exposure studies of a C9-C14 aliphatic solvent with approximately 20% aromatic constituents (Kulig 1990), and there were no neurological effects fol-lowing repeated dermal administration of hydrodesulfurized kerosene (Breglia et al 2014). 21 In a carcinogenicity test of Stoddard solvent Type IIC, conducted by the NTP (2004), there was an elevated frequency of pheochromocytoma in male rats and hepatocellular adenoma in female mice.…”
Section: Heavy Aliphatic Solvents (C9-c20)mentioning
confidence: 99%
See 3 more Smart Citations